2016
DOI: 10.1039/c6ra11409a
|View full text |Cite
|
Sign up to set email alerts
|

Biodirected synthesis of palladium nanoparticles using Phoenix dactylifera leaves extract and their size dependent biomedical and catalytic applications

Abstract: Graphical representation of green synthesis of PdNPs and their biological and catalytic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…The PdNPs have enormous catalytic potential in various organic transformations, including Suzukicross, Mizoroki-Heck, Stille, and Sonogashira coupling reactions. [9][10][11] However, the application of PdNPs in the biomedical field is yet to be adequately investigated, although the green-synthesized PdNPs possess remarkable antioxidant 12,13 and antimicrobial activities. 12,14 Plant-derived PdNPs seem to have potential for application in cancer therapy because these compounds are also toxic to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The PdNPs have enormous catalytic potential in various organic transformations, including Suzukicross, Mizoroki-Heck, Stille, and Sonogashira coupling reactions. [9][10][11] However, the application of PdNPs in the biomedical field is yet to be adequately investigated, although the green-synthesized PdNPs possess remarkable antioxidant 12,13 and antimicrobial activities. 12,14 Plant-derived PdNPs seem to have potential for application in cancer therapy because these compounds are also toxic to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic mechanism for the synthesis of a ZnO Nanoparticles and b ZnO-Ag nanocomposite (Idea from work of Ahmad et al[29] and Mohammed et al[28])…”
mentioning
confidence: 99%
“…21 Smaller and spherical nanoparticles were observed to have more antibacterial effects compared to larger and irregular shaped nanoparticles. 21 At 10 À9 M concentration, Pd has also been reported to exhibit toxicity against Gram-positive bacteria such as Staphylococci, while at concentrations above 10 À9 M, it exhibits toxicity towards Gram-negative bacteria. 23 Two fungi, Aspergillus avus and Candida albicans have previously been tested against PdNPs as well.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few studies that have been conducted on PdNPs for their antimicrobial capabilities. [21][22][23][24] Tahir et al demonstrated the use of biosynthesized PdNPs as antibacterial compounds against Pseudomonas aeruginosa. 21 Smaller and spherical nanoparticles were observed to have more antibacterial effects compared to larger and irregular shaped nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation